PERAN BRAND IMAGE MEMEDIASI SOCIAL MEDIA MARKETING TERHADAP KEPUTUSAN PEMBELIAN - Narayana, Kompyang Gede Sathya; Rahanatha, Gede Bayu (E-Jurnal Manajemen; Vol 9 No 5 (2020), 2020)
The purpose of this study was to determine the role of brand image mediating the effect of social media marketing on purchasing decisions on Denara Bali consumers. This research was conducted in Denpasar City by using a sample of 120 respondents who had already purchased Denara Bali products and had followed and had communicated with Instagram @denarabaliofficial admin, with non-probability sampling techniques with purposive sampling method. Data collection was carried out through questionnaires. The analysis technique used in this research is path analysis and sobel test. The results of this study found that social media marketing had a positive and significant effect on brand image. Social media marketing has a positive and significant influence on purchasing decisions. Brand image has a positive and significant influence on purchasing decisions. Brand image is a mediating variable of the influence between social media marketing on purchasing decisions on Denara Bali consumers in Denpasar City. Keywords : social media marketing, brand image, purchasing decisions